Reactive oxygen species: balancing agents in plants - Alam, Pravej; Faizan, Mohammad; Arif, Yamshi; Azzam, Maged M.; Hayat, Shamsul; Afzal, Shadma; Albalawi, Thamer (Frontiers in Plant Science, 2025)
Reactive oxygen species (ROS) are highly reactive molecules derived from molecular oxygen, playing a dual role in plant systems as both signaling molecules and potential agents of cellular damage. This comprehensive review highlights the fundamental aspects of ROS biology in plants, beginning with the definition and chemical nature of ROS, followed by an in-depth discussion of their various types, including singlet oxygen (1O2), superoxide radicals (O2•−), hydrogen peroxide (H2O2), and hydroxyl radicals (•OH). The review outlines the primary sites of ROS production within plant cells, such as mitochondria, chloroplasts, and peroxisomes, and explains their integral roles throughout the plant life cycle, encompassing growth, development, and senescence. Furthermore, the involvement of ROS in cell-cycle regulation, cell division, and programmed cell death is discussed, emphasizing their critical role in maintaining cellular homeostasis. The review also sheds light on ROS-mediated signaling pathways and their interactions with key plant hormones, including strigolactones, salicylic acid, brassinosteroids, jasmonic acid, and karrikins, highlighting the complexity of ROS-hormone cross talk in regulating stress responses and development. The damaging effects of uncontrolled ROS accumulation on DNA, lipids, proteins, and enzymes are thoroughly examined, underscoring their potential to disrupt cellular functions. Methods for detecting ROS in plant tissues are briefly presented, offering insights into current techniques used for quantifying and visualizing ROS. Overall, this review provides a detailed understanding of ROS dynamics in plant biology and serves as a valuable reference for future research aimed at manipulating ROS signaling to enhance plant resilience and productivity.